1996
DOI: 10.1002/(sici)1099-1085(199604)10:4<479::aid-hyp406>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Approach to Modelling Hydrology and Water Quality in Glacierized Catchments

Abstract: The results are summarized of an integrated investigation of glacier geometry, ablation patterns, water balance, meltwater routing, hydrochemistry and suspended sediment yield. The ultimate objective is to evaluate the assumptions of lumped, two-component mixing models as descriptors of glacier hydrology, and to develop a semi-distributed physically based model as an alternative. The results of the study demonstrate that a reconstruction of probable subglacial drainage alignments can be achieved through a comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 19 publications
6
66
0
Order By: Relevance
“…Additionally, the larger volumes of water passing through the subglacial system may facilitate turbulent incidental contact that allows the meltwaters to mobilize terrestrial sources of DOC at the glacier base (i.e., previously overridden soil and vegetation). Previous work in alpine catchments has illustrated that suspended sediment concentrations increase throughout a melt season as sediment sources are accessed by an extending and integrating subglacial drainage network (Clifford et al, 1995;Richards et al, 1996). This reasoning is also consistent with previous fluorescence spectroscopy work by at a polythermal Canadian high Arctic glacier, which showed that the late season subglacial meltwaters bear a terrestrially-derived signature.…”
Section: Implications For Understanding Subglacial Flow Regimessupporting
confidence: 89%
See 1 more Smart Citation
“…Additionally, the larger volumes of water passing through the subglacial system may facilitate turbulent incidental contact that allows the meltwaters to mobilize terrestrial sources of DOC at the glacier base (i.e., previously overridden soil and vegetation). Previous work in alpine catchments has illustrated that suspended sediment concentrations increase throughout a melt season as sediment sources are accessed by an extending and integrating subglacial drainage network (Clifford et al, 1995;Richards et al, 1996). This reasoning is also consistent with previous fluorescence spectroscopy work by at a polythermal Canadian high Arctic glacier, which showed that the late season subglacial meltwaters bear a terrestrially-derived signature.…”
Section: Implications For Understanding Subglacial Flow Regimessupporting
confidence: 89%
“…In alpine glaciers, subglacial flowpaths seasonally evolve from a delayed-flow (channelized system) to a quick-flow (distributed system) drainage (Paterson, 1994;Richards et al, 1996). However, the seasonal evolution of subglacial drainage is poorly constrained for the GrIS.…”
Section: Introductionmentioning
confidence: 99%
“…On Midtdalsbreen storage occurs throughout the period of measurement (22 June -30 August, 1987), also implying that net release must occur during the cooler part of the year. Similarly, Richards et al (1996) show water balance calculations for Haut Glacier d'Arolla, Switzerland where storage occurs during the first part of the drainage season only to revert to release during the later half of the melt season. They attribute this change to the seasonal reorganisation of subglacial drainage rather than firn and snow storage.…”
Section: Seasonal Water Balancementioning
confidence: 99%
“…The idea was to monitor drainage system evolution by using changes in the hydrochemistry of the bulk meltwaters leaving the glacier, in tandem with an intensive programme of dye injections into multiple supraglacial streams and moulins that would provide a direct measure of water transit times though the glacier and their changes over a full melt season (Richards et al, 1996). HGA ( Fig.…”
Section: The First Haut Glacier D'arolla Project (Mt)mentioning
confidence: 99%
“…As a result, we were limited to conducting one experiment every 2-3 days. We were also detecting the dye by manually collecting samples from the stream and pouring Tranter et al, 1996). them through a fluorometer, which meant that someone had to sit by the stream for hours at a time to collect and run the samples.…”
Section: Dye Tracing Experiments -A Learning Experience In Norway (Ms)mentioning
confidence: 99%